Single‐Atom Cu Stabilized on Ultrathin WO2.72 Nanowire for Highly Selective and Ultrasensitive ppb‐Level Toluene Detection - Peng Wang; Shisong Guo; Zhixiang Hu; Licheng Zhou; Tiankun Li; Shiliang Pu; Hui Mao; Hong Cai; Zhenfeng Zhu; Bingbing Chen; Hua‐Yao Li; Huan Liu (Advanced Science, 2023)
Abstract Various catalysts are developed to improve the performance of metal oxide semiconductor gas sensors, but achieving high selectivity and response intensity in chemiresistive gas sensors (CGSs) remains a significant challenge. In this study, an in situ‐annealing approach to synthesize Cu catalytic sites on ultrathin WO2.72 nanowires for detecting toluene at ultralow concentrations (Ra/Rg = 1.9 at 10 ppb) with high selectivity is developed. Experimental and molecular dynamic studies reveal that the Cu single atoms (SAs) act as active sites, promoting the oxidation of toluene and increasing the affinity of Cu single‐atom catalysts (SACs)‐containing sensing materials for toluene while weakening the association with carbon dioxide or water vapor. Density functional theory studies show that the selective binding of toluene to Cu SAs is due to the favorable binding sites provided by Cu SAs for toluene molecules over other gaseous species, which aids the adsorption of toluene on WO2.72 nanowires. This study demonstrates the successful atomic‐level interface regulation engineering of WO2.72 nanowire‐supported Cu SAs, providing a potential strategy for the development of highly active and durable CGSs.